Anti TNF therapy in rheumatoid arthritis - Feldmann, Marc (Henry Stewart Talks, 2007)
Immunological basis of rheumatoid arthritis (RA), Up-regulated cytokine expression is of major importance in RA, Analysis of the disordered regulation shows that TNF blockade restored normal cytokine and destructive molecule levels and thus defined TNF as a therapeutic target, Animal models of arthritis, Clinical trials, TNF has major input into leucocyte recruitment, it is thus the body's fire alarm, TNF blockade and Crohn's disease, ulcerative colitis, ankylosing spondylitis, psoriasis, psoriatic arthritis and juvenile RA, This represents the first major use for monoclonal antibodies in chronic diseases
Archived at 2019/06/13